9 COCL2 induced cardiotoxicity associated with cocr alloy orthopaedic implants- an in vivo and an in vitro study. (1st April 1997) - Laovitthayanggoon, Sarunya; Grant, M Helen; Henderson, Catherine J; Tate, Rothwelle J; Currie, Susan
Abstract : Cobalt/chromium (Co/Cr) alloy metal-on-metal bearings used in prosthetic hip replacements can cause adverse effects in some patients because they release metal ions into the bloodstream during wear. Co toxicity may be a cause of many severe systemic manifestations including neurologic and cardiac symptomatology. This study examines the effects of chronic Co exposure in rats treated for 28 days with CoCl2 (single i.p. injection of 1 mg/kg, daily) and examines Co uptake in vitro into primary adult cardiac fibroblasts (CFs). Co treatment was associated with accumulation into various organs with significant increases detected in liver, kidney and heart (245.31±23.64, 204.80±11.19 and 41.04±4.77 µg/L respectively). Echocardiography performed on the same animals showed functional changes correlating with compromised cardiac contractility. Fractional shortening was significantly reduced in CoCl2 –treated rats following 28 days treatment when compared with control animals (54.01%±0.90%% vs 60.29±0.53%%, n=6, p≤0.01) and there was evidence of diastolic dysfunction. In order to investigate how Co may accumulate in the heart, primary adult CFs were isolated and uptake of CoCl2 into CFs was compared with uptake into a standard fibroblast 3T3 cell line (3T3s). Uptake of metal ions was measured using inductively coupled plasma mass spectrometry. Co uptake into both 3T3s and CFs increased to between 0–50 and 0–120 µg/L, respectively as the medium concentration of Co (0–300 µM) increased. Interestingly, uptake of Co into CFs was significantly greater than into 3T3 cells. The greater accumulation of CoCl2 into CFs suggests that Co ions in vivo could accumulate in these cells and have functional consequences on cardiac performance. Overall, our data provides strong evidence that Co accumulates in the heart resulting in cardiac dysfunction. Importantly, we have shown for the first time that Co could accumulate in the heart via efficient uptake into CFs. Future work will focus on determining the underlying mechanism for uptake which could have important therapeutic implications.